Food Safety on the Farm: Good Agricultural Practices and Good Handling Practices – Water - Keith R. Schneider; Renée M. Goodrich-Schneider; Douglas L. Archer (EDIS, 2006)
(also in FYCS Descriptions). FSHN06-02, a 4–page factsheet by Keith R. Schneider, Renee Goodrich Schneider, and Douglas L. Archer, provides detailed guidelines to commercial producers and packers of fresh fruits and vegetables on how to use water in production and handling in order to produce a clean, safe product. Published by the UF Department of Food Science and Human Nutrition, November 2006.